Fluorescence emission originated from the H-aggregated cyanine dye with chiral gemini surfactant assemblies having a narrow absorption band and a remarkably large Stokes shift. Issue 63 (24th July 2017) - Ryu, Naoya; Okazaki, Yutaka; Pouget, Emilie; Takafuji, Makoto; Nagaoka, Shoji; Ihara, Hirotaka; Oda, Reiko
Abstract : A cyanine dye formed chiral H-aggregates with a narrow absorption band on gemini surfactant chiral assemblies and showed fluorescence emission with a remarkably large Stokes shift. Abstract : We demonstrate that the fluorescence emission that originated from a cyanine dye forming H-aggregates with a narrow absorption band and a remarkably large Stokes shift can be induced by symmetry breaking. The H-aggregate formation was successfully induced using chirally assembled cationic gemini surfactants with enantiomeric tartrate counterions as templates in water.